2020
DOI: 10.1002/uog.21940
|View full text |Cite
|
Sign up to set email alerts
|

Third‐trimester uterine artery Doppler for prediction of adverse outcome in late small‐for‐gestational‐age fetuses: systematic review and meta‐analysis

Abstract: CONTRIBUTION What are the novel findings of this work?This study provides evidence of a higher risk of adverse outcome in suspected third-trimester small-forgestational-age (SGA) fetuses with abnormal uterine artery Doppler, which is comparable to that in late SGA fetuses with abnormal cerebroplacental ratio. What are the clinical implications of this work?The findings from this study should enable clinicians to assess the risk of adverse perinatal outcome in SGA fetuses, using the likelihood ratios of abnorma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 53 publications
3
30
1
Order By: Relevance
“…A systematic review has shown that model performance for screening for gestational hypertensive disorders varies with the use of different maternal, fetal and placental characteristics among low-risk and high-risk populations [40]. A meta-analysis comprising seventeen observational studies showed that among SGA fetuses and newborns, which is considered a high-risk population, concluded that an increased UtA-PI increased the risk of adverse perinatal outcomes, but because of limited predictive capacity as a standalone test, UtA-PI should be combined in combination with other tests [41]. Although causality cannot be established in observational research, these findings suggest that maternal age may, through suboptimal utero-placental vascular function, influence pregnancy outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…A systematic review has shown that model performance for screening for gestational hypertensive disorders varies with the use of different maternal, fetal and placental characteristics among low-risk and high-risk populations [40]. A meta-analysis comprising seventeen observational studies showed that among SGA fetuses and newborns, which is considered a high-risk population, concluded that an increased UtA-PI increased the risk of adverse perinatal outcomes, but because of limited predictive capacity as a standalone test, UtA-PI should be combined in combination with other tests [41]. Although causality cannot be established in observational research, these findings suggest that maternal age may, through suboptimal utero-placental vascular function, influence pregnancy outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…183 There are many conceptual explanations to support thirdtrimester ultrasound as it can assist in the diagnosis of clinically significant findings other than FGR, including fetal malpresentation, 184 disorders of amniotic fluid, and fetal anomalies, 185,186 especially when combined with Doppler measurements and biochemical markers. 95,[187][188][189] However, there is no evidence that this information improves outcomes when performed routinely in lowrisk pregnancies.…”
Section: Is There a Role For Routine Third-trimester Ultrasound To mentioning
confidence: 99%
“…However, in the group of FGR by both standards, the induction rate was even higher (56%) but the perinatal outcomes significantly poorer. Second, we do not have information on the uterine Doppler, which is also a Doppler parameter that has been proposed to define FGR as a reflection of the placental functioning from the maternal side [28]. Likewise, we do not have information on the placental findings to compare our study groups.…”
Section: Discussionmentioning
confidence: 98%